Health systems strengthening: assessing the influence of organizational factors of community health volunteers on use of community based health information systems in selected counties, Kenya - Mambo, Susan N.; Odhiambo-Otieno, George W.; Ochieng’-Otieno, George; Mwaura-Tenambergen, Wanja (International Journal Of Community Medicine And Public Health, 2021)
Background: WHO places health information as a key pillar of an effective health system (HS). HS strengthening has become a key focus of many nations. A paradigm shift from being disease specific focus to holistic strengthening of pillars of a HS. Kenya’s functionality of CbHMIS (community based health information systems) stands at 55% down from 64% in year 2015, majorly contributed to by organization of community health volunteers (CHVs) work. The aim was to establish influence of organizational factors of CHVs on CbHMIS use in Kenya. Methods: A cross-sectional design which employed both quantitative and qualitative approaches was used. Kiambu, Kajiado and Nairobi counties formed the study location. A systematic random sample of 366 respondents was drawn. Multistage sampling was used to identify the community units (CUs). Ethical clearance was obtained from KEMU, ethics and research committee (SERC), national commission for science, technology and innovation (NACOSTI) gave a research permit. 3 FGDs and 6 KIIs were conducted. Quantitative data was analyzed using SPSS version 23 to generate univariate and bivariate analysis at p<0.05 significance level. Qualitative data was analyzed using content analysis. Results were presented in form of graphs, tables, figures and narration. Results: Use of CbHMIS stood at 56.6%. Organizational factor explains 39.9% (R2=0.399) of total variations in the use of CbHMIS. Organizational factors of the CHVs were found to positively and significantly influence use of CbHMIS. Conclusions: Organizational factors influences use of CbHMIS by CHV. Government/partners to build CUs capacity on sustainable resource mobilization strategies.